The effect of exercise-intensity on skeletal muscle stress kinase and insulin protein signaling. - Lewan Parker; Adam Trewin; Itamar Levinger; Christopher S Shaw; Nigel K Stepto (PLoS ONE)
Background Stress and mitogen activated protein kinase (SAPK) signaling play an important role in glucose homeostasis and the physiological adaptation to exercise. However, the effects of acute high-intensity interval exercise (HIIE) and sprint interval exercise (SIE) on activation of these signaling pathways are unclear. Methods Eight young and recreationally active adults performed a single cycling session of HIIE (5 x 4 minutes at 75% Wmax), SIE (4 x 30 second Wingate sprints), and continuous moderate-intensity exercise work-matched to HIIE (CMIE; 30 minutes at 50% of Wmax), separated by a minimum of 1 week. Skeletal muscle SAPK and insulin protein signaling were measured immediately, and 3 hours after exercise. Results SIE elicited greater skeletal muscle NF-κB p65 phosphorylation immediately after exercise (SIE: ~40%; HIIE: ~4%; CMIE; ~13%; p < 0.05) compared to HIIE and CMIE. AS160Ser588 phosphorylation decreased immediately after HIIE (~-27%; p < 0.05), and decreased to the greatest extent immediately after SIE (~-60%; p < 0.05). Skeletal muscle JNK (~42%; p < 0.05) and p38 MAPK (~171%; p < 0.05) phosphorylation increased, and skeletal muscle AktSer473 phosphorylation (~-32%; p < 0.05) decreased, to a similar extent immediately after all exercise protocols. AS160Ser588 phosphorylation was similar to baseline three hours after SIE (~-12%; p > 0.05), remained lower 3 hours after HIIE (~-34%; p < 0.05), and decreased 3 hours after CMIE (~-33%; p < 0.05). Conclusion Despite consisting of less total work than CMIE and HIIE, SIE proved to be an effective stimulus for the activation of stress protein kinase signaling pathways linked to exercise-mediated adaptation of skeletal muscle. Furthermore, post-exercise AS160Ser588 phosphorylation decreased in an exercise-intensity and post-exercise time-course dependent manner.